The governance of public and non-profit organisations : what do boards do? - Cornforth, Chris (Routledge studies in the management of voluntary and non-profit organizations ;, 2003)
Governing boards play a crucial role in ensuring that public and non-profit organizations are publicly accountable and perform well. Until now, there have been relatively few detailed empirical studies of what boards do in practice, but this book fills that gap by bringing together analyses based upon some of the best recent empirical studies. Using a new theoretical framework that highlights the paradoxical nature of governance, the book throws light on the questions at the heart of recent debates about non-profit boards:are boards publicly accountable or is there a democ.